Intrapancreatic recurrence of intraductal tubulopapillary neoplasm (ITPN) 16 years after the initial surgery for noninvasive ITPN: a case report - Kiyoshi Saeki; Yoshihiro Miyasaka; Yoshihiro Ohishi; Takeo Yamamoto; Ryota Matsuda; Naoki Mochidome; Yasuhisa Mori; Kohei Nakata; Takao Ohtsuka; Kousei Ishigami; Yosuke Minoda; Yutaka Koga; et al. (Surgical Case Reports, 2018)
Abstract Background Intraductal tubulopapillary neoplasm (ITPN) is a rare pancreatic intraductal neoplasm. It is characterized by a tubulopapillary growth pattern, entirely high-grade atypical cells, minimal cytoplasmic mucin, and no obvious luminal mucin secretion. Most of its biological nature remains unclear. Case presentation We herein report a case of intrapancreatic recurrence of ITPN in the remnant pancreas of a patient who underwent pancreatoduodenectomy 16 years previously for a noninvasive intraductal pancreatic head tumor. We reexamined the primary tumor and compared it with the most recently resected specimen. Histologically, the primary tumor showed a tubulopapillary growth of high-grade atypical cells with scanty cytoplasmic mucin, which was similar to the recently resected specimen except for the invasive area. Immunohistochemically, the neoplastic cells in both specimens showed focal staining of MUC1 and positivity for MUC6 but negativity for MUC2, MUC5AC, CDX2, and trypsin. Molecular analysis revealed no KRAS/GNAS/BRAF/PIK3CA mutations in either of the specimens. Conclusions These findings of the original tumor and recently resected tumor were compatible with the features of ITPN. Thus, recurrence is possible even for a primary noninvasive ITPN, and long-term surveillance is recommended.